DAMPAK IMPLEMENTASI KEBIJAKAN LINGKUNGAN TERHADAP KUALITAS UDARA DI PERKOTAAN: EFEKTIFITAS KEBIJAKAN, HAMBATAN DAN TUNTUTAN - Mansa, Nurain; Djafar, Aprilyawati; Dako, Siti Nurul Fadilah (Journal of Governance and Public Administration, 2025)
Air quality in urban areas continues to decline due to rapid urbanization, the surge in motor vehicle use, and uncontrolled industrial activities. In response, governments have introduced various environmental policies, including emission regulations, the development of environmentally friendly transportation, and the expansion of green open spaces. However, the effectiveness of these policies remains in question, largely due to structural and social implementation barriers. This study aims to comprehensively examine the impact of environmental policy implementation on air quality in major Indonesian cities, focusing on two key aspects: the barriers to implementation and the emerging demands for policy reform and improvement.